Analisis Preferensi Petani Terhadap Alih Fungsi Lahan Pertanian Menjadi Jalur Rel Kereta Api Di Desa Salenrang Kecamatan Bontoa Kabupaten Maros - Amri, Milmi Ulil; Azisah, Azisah; Pata, Abd. Asis (Universitas Muslim Maros, 2024)
This study aims to determine farmers' preferences for the conversion of agricultural land into railway lines in Salenrang Village, Bontoa District, Maros Regency. This type of research uses a quantitative descriptive method. The population in this study was 349 farmers in Salenrang Village, Bontoa District, Maros Regency. The respondents were taken using the purposive sampling method, with 34 respondents whose land had been converted into railway lines. The data used were obtained from interviews and questionnaires filled out by respondents. The results of the study showed the level of farmer preference for the conversion of agricultural land into railway lines in Salenrang Village, Bontoa District, Maros Regency, namely on internal factors with a score of 76.6 while on external factors with a score of 74.4 in the less satisfied category with an average of 75.5.